Dermoid cyst of the spermatic cord: A rare cause of benign inguinal lump - Aslam, M; Kheradmund, F; Patel, N; Turner, G; Cranston, D (2009)
Dermoid cyst of the spermatic cord is an extremely rare pathology seen at the urological clinic. We present the case of a 26-year-old man who presented with a groin lump, thought to be a lipoma or a hydrocoele of the cord. The final histopathological analysis established the diagnosis of a dermoid cyst. © 2009 Canadian Urological Association.